2015
DOI: 10.1007/s11356-015-5665-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of rabbit manure biofertilizer in barley crop yield

Abstract: The quality of biofertilizers is usually assessed only in terms of the amount of nutrients that they supply to the crops and their lack of viable pathogens and phytotoxicity. The goal of this study was to determine the effectiveness of a liquid biofertilizer obtained from rabbit manure in terms of presence of pathogens, phytotoxicity, and its effect on the grain yield and other agronomic traits of barley (Hordeum vulgare L.). Environmental effects of the biofertilizer were also evaluated by following its influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…The P T content was similar in both biofertilizers, ours and Quintanar-Orozco s et al [48], but ours had higher N T , K, and Mg concentrations, and lower Cu and Fe contents (Table 2). Due to the high water content of nopal, nopal-based biofertilizers' nutrient content is lower than that of organic fertilizers prepared from animal wastes [63] or other plants by composting [64]. Besides nutrients, biofertilizer provides beneficial microorganisms that improve the use of nutrients.…”
Section: Biochar and Biofetilizer Characteristicsmentioning
confidence: 99%
“…The P T content was similar in both biofertilizers, ours and Quintanar-Orozco s et al [48], but ours had higher N T , K, and Mg concentrations, and lower Cu and Fe contents (Table 2). Due to the high water content of nopal, nopal-based biofertilizers' nutrient content is lower than that of organic fertilizers prepared from animal wastes [63] or other plants by composting [64]. Besides nutrients, biofertilizer provides beneficial microorganisms that improve the use of nutrients.…”
Section: Biochar and Biofetilizer Characteristicsmentioning
confidence: 99%
“…Consequently, the effective method to reduce the soil pollution is crucial and to increase the food crop production as well as the quality of the food crop is essential. The use of biofertilizers is highly recommended based on the many literature [7,[15][16][17][18] found that are in great support of such farming practice to reduce the soil pollution. In this short communication paper, allow me to introduce one of the best companies in green biotechnology in Asia.…”
Section: Short Communicationmentioning
confidence: 99%
“…It is possible that this lack of uniformity is related to the low availability of data regarding the chemical composition of these inputs and the raw materials, which makes it difficult to plan for the elaboration of formulations. In addition, due to different possible combinations among raw materials to obtain a biofertilizer, it is expected that there would be products with a wide range of nutrient contents [11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. In general, two major groups of waste sources have been used to produce biofertilizers: One is based on manure from different animals [21,22], and the other is composed of agro-industrial and household wastewater, such as cassava, olive, or domestic waste processing [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that the main reason for the second group of biofertilizers is the great diversity of available microorganisms (among which has been identified bacteria of the genera Pseudomonas, Bacillus, Gluconacetobacter, and Corynebacterium, as well as many other fungi and yeasts) [25]. When applied to plants, these biofertilizers stimulate physiological or natural processes that increase nutrient absorption, since such bacteria stimulate the production of metabolites, related directly to the growth of the plant (e.g., auxins, gibberellins, and cytokinins) [26]. They also synthesize antibiotics, siderophores, and hydrocinnamic acid that reduce pathogen activities [27].…”
Section: Introductionmentioning
confidence: 99%